SEX DIFFERENTIATION AND GROWTH PERFORMANCE TRIALS OF TWO GENOTYPES OF TILAPIA ADMINISTERED WITH ANDROGENIC HORMONE - Didik Ariyanto; Komar Sumantadinata; Agus Oman Sudrajat (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2010)
The aim of this study was to know the effect of dietary administration of androgenic hormone methyltestosterone on two sex genotypes of Nile tilapia i.e. XX and XY genotype, especially to sex ratio, growth rate, survival rate, food conversion ratio and harvest yield. XX genotype was obtained from XX male matted with XX normal female, and XY genotype was obtained from YY super-male matted with XX normal female. Methyltestosterone was administered seven days after larvae hatching for 28 days. After that, the fish were reared in hapas for 60 days and then placed in growout ponds for 120 days period. As check population, mixed sex genotype was used consisting of 50% XX genotype and 50% XY genotype. The result showed that dietary administration of methyltestosterone in XX genotype significantly increased male proportion about 82.42%, compared with control XX population (7.55%). The same treatment in genotype XY did not significantly increase the proportion of male (85.13%), compared with control XY population (79.81%). In grow-out ponds, all male population (XY genotype and sex reversed from XX genotype) have better growth rate than all female and mixed sex populations. Dietary administration of methyltestosterone in both of XX and XY genotypes increased growth rate of these populations resulting in the increased of total biomass at harvest time.